Hanjeli, Rosela and Stevia Cultivation Training in Sasak Panjang Village, Bogor Regency: Pelatihan Budidaya Hanjeli, Rosela dan Stevia di Desa Sasak Panjang Kabupaten Bogor - Roshamur Cahyan Forestrania; Febrina Amelia Saputri; Kartika Citra Dewi Permata Sari; Nisa Maria; Taufiq Indra Rukmana; Hindun Wilda Risni; Donna Maretta Ariestanti; Berna Elya (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The community service program in Sasak Panjang Village, Bogor Regency, started with an assessment of the problems and potency of the village. These problems are the lack of close access to health care services and the failure to cultivate Family Medicinal Plants (FMP). According to The Ministry of Education and Culture program focus in 2022, it is necessary to carry out community service activities to increase the independence of public health efforts. Therefore, a community service program was performed through education, training, and mentoring for FMP cultivation to solve these problems. The success indicator of this activity was that the communities in Sasak Panjang were trained to cultivate the FMP (adlay, roselle, and stevia), and all crops could grow well. The outcome of this program is likely to encourage the independence of local community health initiatives in Sasak Panjang Village, Bogor Regency.